Simulation of stochastic transport and deposition of seed runaway electrons during disruption mitigation - Yuxiang Sun; Bo Li; Feng Wang; Di Hu; Yue Yuan; Long Cheng; Yuhao Li; the JOREK Team (Nuclear Fusion)
Runaway electrons (REs) during the Current Quench can significantly impact the operational limits and component lifetime of future high-performance tokamaks such as ITER. Localized, uncontrolled REs deposition can result in serious damage to first wall surfaces and structures in the devices, especially if the REs replaces the bulk electrons as the main current carrier. One way to avoid such current replacement is to deplete the seed REs within the plasma through stochastic trajectory loss before they have time to avalanche. To investigate such stochastic transport behavior as part of the ITER disruption mitigation scheme, we carry out guiding center simulations of the seed REs with conservative higher-order magnetic moments using the PTC code based on fluid fields produced by JOREK simulations. We focus on an ITER plasma after Shattered Pellet Injection, which experiences breaking-up and healing of flux surfaces, and investigate the RE transport properties as the stochasticity evolves. Self-similar density profiles and exponential decay of seed REs are found for cases with sufficiently stochastic magnetic field. The diffusion of seed REs with various momentum, pitch angle and initial location is investigated and their corresponding transport coefficients are obtained statistically through the simulations and compared with the effective RE radial flux. We also examine their timescale of loss and compare it with that of the RE avalanche to estimate the efficiency of stochastic RE depletion during the mitigation process. Finally, using a realistic 2D wall, we present the deposition pattern of REs on the first wall to estimate its asymmetry.